2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM) 2016
DOI: 10.1109/speedam.2016.7526006
|View full text |Cite
|
Sign up to set email alerts
|

Wireless power transfer impact on data channel

Abstract: Abstract-This paper presents measurement results and analysis of the interference produced by the high-power electromagnetic field in a wireless energy transfer system. Through this analysis it is expected to be possible to evaluate the influence of the strong electromagnetic field on the data transmission channel. The wireless power transfer aimed at electric vehicles battery charging receives a great deal of attention in the recent years. However, the performance of those systems depends on the exchange of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, data signal is realized at much higher frequencies, particularly in the GHz order [14,15]. The experimental results of measurement and the analysis of the electromagnetic fields generated by WPT system as well as their possible interaction on data transmission channel are reported in [13,14]. They confirmed that there is no substantial impact from WPT system operating at 20 kHz frequency on data transfer channel operating at 2.4 GHz frequency.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…On the other hand, data signal is realized at much higher frequencies, particularly in the GHz order [14,15]. The experimental results of measurement and the analysis of the electromagnetic fields generated by WPT system as well as their possible interaction on data transmission channel are reported in [13,14]. They confirmed that there is no substantial impact from WPT system operating at 20 kHz frequency on data transfer channel operating at 2.4 GHz frequency.…”
Section: Introductionmentioning
confidence: 63%
“…At high frequency, electromagnetic interferences (EMI) become an important issue where the high-intensity EMF can have a harmful impact not only on the surrounding equipment and the exchange of the data between the transceivers but also on the human safety. In fact, to figure out the range of interference generated by WPT equipment, serval studies are proposed [12][13][14][15]. Firstly, a study related to the electromagnetic emissions from WPT effects are discussed in [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model with the given setup and specifications was used for an experimental verification of the results of a previous research [21,22]. The equipment for the measurement of the electric field was composed by a WET power converter and a measuring instrument Narda SRM-3000 (Selective Radiation Meter).…”
Section: Methodsmentioning
confidence: 99%
“…the operation frequency, the required power, the vehicle identification and the payment information. However, a high intensity EMF generated by WPT system may introduce highly undesired influence on the communication channel which could be a severe problem [12]- [13].…”
Section: Introductionmentioning
confidence: 99%